Contemporary sample stacking in analytical electrophoresis. Issue 1 (3rd December 2012) - Šlampová, Andrea; Malá, Zdena; Pantůčková, Pavla; Gebauer, Petr; Boček, Petr; Rassi, Ziad El
<x xml:space="preserve">Abstract</x> Sample stacking is a term denoting a multifarious class of methods and their names that are used daily in CE for online concentration of diluted samples to enhance separation efficiency and sensitivity of analyses. The essence of these methods is that analytes present at low concentrations in a large injected sample zone are concentrated into a short and sharp zone (stack) in the separation capillary. Then the stacked analytes are separated and detected. Regardless of the diversity of the stacking electromigration methods, one can distinguish four main principles that form the bases of nearly all of them: (i) Kohlrausch adjustment of concentrations, (ii) pH step, (iii) micellar methods, and (iv) transient ITP. This contribution is a continuation of our previous reviews on the topic and brings an overview of papers published during 2010–2012 and relevant to the mentioned principles (except the last one which is covered by another review in this issue).